Recent Innovations in Post-harvest Preservation and Protection of Agricultural Products - Maier, Dirk E. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The global food supply chain relies on engineered systems, operational practices, and logistics to preserve, protect, process, and deliver agricultural crops along complex supply lines from farmers in low-, middle-, and high-income countries to markets around the world. Food and nutrition security is compromised by post-harvest losses (and food waste) that have been estimated to be as high as 20% in durable and 40% in perishable crops. Preserving crops using technologies and practices such as timely harvesting, evaporative cooling, cold and frozen storage, drying, and dehydrating, and protecting crops using technologies and practices such as damage-less handling, controlled and modified atmosphere storage, non-chemical heat and gas treatment, plant-derived protective films for individual fruits and vegetables, and improved packaging containers are critical to preserving nutrients, improving livelihoods, and realizing an efficient food system. This Special Issue aims to cover recent progress and innovations in science, technology, engineering, operational practices, and logistics related to post-harvest preservation and protection of durable and perishable agricultural crops. It seeks contributions that improve effectiveness, efficiency, reliability and sustainability in post-harvest handling of crops from field to end use that preserve product quality and result in foods and feeds which are nutritious and safe for human and animal consumption.